2022
DOI: 10.1007/s10992-022-09651-x
|View full text |Cite
|
Sign up to set email alerts
|

Paraconsistent Metatheory: New Proofs with Old Tools

Abstract: This paper is a step toward showing what is achievable using non-classical metatheory—particularly, a substructural paraconsistent framework. What standard results, or analogues thereof, from the classical metatheory of first order logic(s) can be obtained? We reconstruct some of the originals proofs for Completeness, Löwenheim-Skolem and Compactness theorems in the context of a substructural logic with the naive comprehension schema. The main result is that paraconsistent metatheory can ‘re-capture’ versions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…So this is one example, which seems to have some promise from field testing, but it is not presented here as final or definitive. It seems likely that there are improvements and additions (for example, restricted quantifiers (Beall et al, 2006;Badia et al, 2022), using sparingly below) that will in future make for a fuller account for framing (paraconsistent) mathematics.…”
Section: } Obeying Some Limited Form Of Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So this is one example, which seems to have some promise from field testing, but it is not presented here as final or definitive. It seems likely that there are improvements and additions (for example, restricted quantifiers (Beall et al, 2006;Badia et al, 2022), using sparingly below) that will in future make for a fuller account for framing (paraconsistent) mathematics.…”
Section: } Obeying Some Limited Form Of Inductionmentioning
confidence: 99%
“…2 with respect to LP, namely that definitions 5 and 7 are equivalent. This is a modification of (Weber et al, 2016;Badia et al, 2022;Omori and Weber, 2023).…”
Section: Soundness and Completenessmentioning
confidence: 99%
See 1 more Smart Citation
“…But a metatheoretical proof of a formal system also requires valid inferences. Badia, Weber & Girard (2022) have shown that such a metalogic can be paraconsistent in the sense that a paraconsistent metalogic can 'recapture' famous classical metatheoretical theorems such as Completeness, Löwenheim-Skolem and Compactness in a substructual paraconsistent metatheory.…”
Section: Paraconsistent Metatheorymentioning
confidence: 99%
“…For small steps into a serious nonclassical metatheory, see Rosenblatt (2021b); cf. Weber, Badia, and Girard (2016), Badia, Weber, and Girard (2022). Meyer already attempted some work like this in Meyer (1985).…”
Section: Into the Paraconsistentmentioning
confidence: 99%